The Road Performances Analysis in Jalan Laksamana Bintan, Batam-Indonesia - Gabriel Immanuel; Andri Irfan Rifai; Joewono Prasetijo (International Journal Labs, 2022)
Jalan Laksamana Bintan is a secondary arterial road with high vehicle intensity. They are located in industrial and schooling areas, causing traffic congestion due to many road users. This study aims to determine the performance of the road during adequate working time. This study used the IHCM 1997 method and field surveys to collect data directly. Data was taken at Jalan Laksamana bintan, Batam (Kenki Intersections – Frenkie). The results obtained from the traffic analysis on Thursday, November 10, 2022, 06.30 AM – 07.30 AM with the degree of saturation = 0.5, actual speed = 47.95 km/hour, volume = 3069.45 pcu/hour, capacity = 6082.56, and Level of Services = C. This condition indicates that Jalan Laksamana Bintan is still comfortable and suitable for use by traffic users